2008
DOI: 10.1007/s12043-008-0271-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motion in restricted geometries

Abstract: Molecular dynamics in restricted geometries is known to exhibit anomalous behaviour. Diffusion, translational or rotational, of molecules is altered significantly on confinement in restricted geometries. Quasielastic neutron scattering (QENS) offers a unique possibility of studying molecular motion in such systems. Both time scales involved in the motion and the geometry of motion can be studied using QENS. Molecular dynamics (MD) simulation not only provides insight into the details of the different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In natural environments, they are mostly found confined in porous media like sedimentary rocks such as shale which can profoundly affect their behavior [1,2]. Several studies have reported the effect of nano-confinement on various properties of the adsorbate including its structure, phase behavior and dynamics.…”
Section: Effect Of Temperature and Pressure On The Dynamics Of Nanocomentioning
confidence: 99%
“…In natural environments, they are mostly found confined in porous media like sedimentary rocks such as shale which can profoundly affect their behavior [1,2]. Several studies have reported the effect of nano-confinement on various properties of the adsorbate including its structure, phase behavior and dynamics.…”
Section: Effect Of Temperature and Pressure On The Dynamics Of Nanocomentioning
confidence: 99%
“…Molecular motion under confinement is an interesting topic of research as it entails a variety of peculiar phenomena [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Anomalous size and loading dependence of molecular dynamics of confined fluids in porous media have been reported [6][7][8] , suggesting the need of better understanding how confinement affects not only the structure but also the transport-properties of confined fluids.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this fundamental interest, a study of molecular motion under confinement has practical implications in industries like catalysis and gas recovery. This has resulted in an extensive study of molecular dynamics under confinement. Of particular interest is the dynamics of hydrocarbons confined in porous media , due to their application in catalytic cracking reactions and hydrocarbon recovery. Porous media is classified according to IUPAC as microporous with pores smaller than 2 nm and mesoporous with pores larger than 2 nm in size .…”
Section: Introductionmentioning
confidence: 99%